The Impact of Industry 4.0 on New Product Development in Small and Medium Enterprises: A Review - Kazeem A. BELLO; Adeniyi O. ADESINA; Lukman A. OPEYEMI; Solomon O. UVIASE (FUDMA Journal of Engineering and Technology, 2026)
Industry 4.0 has attracted growing scholarly attention for its potential to change new product development (NPD) in small and medium-sized enterprises (SMEs). However, existing studies remain fragmented, methodologically diverse, and often overly optimistic in their assessment of digital technology adoption. This study presents a structured narrative literature review that critically evaluates how Industry 4.0 technologies influence NPD processes in SMEs. Drawing on peer-reviewed journal articles, conference papers, and conceptual studies sourced from major academic databases, the review synthesises qualitative and quantitative evidence to clarify the nature of Industry 4.0’s impact, the benefits reported, and the challenges encountered by SMEs. The analysis integrates findings across the NPD lifecycle and highlights how firm-level characteristics, digital readiness, and contextual constraints outline outcomes. Rather than aggregating effect sizes, the study emphasises critical comparison, identification of inconsistencies, and recognition of underexplored trade-offs in the literature. The review contributes to theory by consolidating dispersed insights and to practice by offering evidence-informed perspectives for SME managers and policymakers. Generally, the study offers a balanced understanding of Industry 4.0-enabled NPD and isolates key guidelines for future research.
Keywords: Digital transformation, Industry 4.0, Innovation, New product development, Small and medium-sized enterprises.